2020
DOI: 10.1111/mmi.14647
|View full text |Cite
|
Sign up to set email alerts
|

Electrolocation? The evidence for redox‐mediated taxis in Shewanella oneidensis

Abstract: Shewanella oneidensis is a dissimilatory metal reducing bacterium and model for extracellular electron transfer (EET), a respiratory mechanism in which electrons are transferred out of the cell. In the last 10 years, migration to insoluble electron acceptors for EET has been shown to be nonrandom and tactic, seemingly in the absence of molecular or energy gradients that typically allow for taxis. As the ability to sense, locate, and respire electrodes has applications in bioelectrochemical technology, a better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…This is the first example to demonstrate the deposition of two different microbial strains at distinct regions on the same substrate. Our approach takes advantage of insoluble electron acceptor taxis [ 67 ] or the electromigration of S. oneidensis toward the positive electrode during deposition. [ 69 ] By applying a positive potential and introducing a specific strain of S. oneidensis , we can deposit the microbes only on a desired region of the electrode surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first example to demonstrate the deposition of two different microbial strains at distinct regions on the same substrate. Our approach takes advantage of insoluble electron acceptor taxis [ 67 ] or the electromigration of S. oneidensis toward the positive electrode during deposition. [ 69 ] By applying a positive potential and introducing a specific strain of S. oneidensis , we can deposit the microbes only on a desired region of the electrode surface.…”
Section: Resultsmentioning
confidence: 99%
“…Representative examples of 2D and 3D electrode interface layers designed to increase current densities are listed in Table 1. [56][57][58][59][60][61][62][63][64][65][66][67] Although 2D electrode interface layers in MESs usually generate lower absolute biotic current density compared with their 3D counterparts, we found that the improvement of current density using our PEDOT:PSS/PHEA-coated electrode surpassed that of other 2D and 3D interfaces. For example, a 2018 study reported that the steady-state current density increased a factor of 20 using a PEDOT:PSS-based, multilayer biocomposite interface layer.…”
Section: Poly(34-ethylenedioxythiophene)-poly(styrenesulfonate)/ Poly...mentioning
confidence: 99%
“…We use a qualitative assay method to study the long-term EET process to prove this. The oscillation frequency of motile cells infers the rotation of the flagellar motor, which is associated with the proton motive force built by EET. This phenomenon is described as EET-dependent electrokinesis. Here we measure the real-time plasmonic amplitude of a single MR-1@MNP cell during a 400 min EET process.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Therefore, it produces conductive appendages being extensions of the outer cell membrane ( Subramanian et al, 2018 ). Thus, if no mediator is present EET is only possible, if the suspended cells have at least temporary physical contact with the anode ( Harrisa et al, 2010 ; Starwalt-Lee et al, 2021 ). This limitation and the insufficient mediator production are the main reasons that S. oneidensis cannot reach high current densities ( Logan et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%